Analysis Teachers' Efforts and Challenges in Implementing Multisensory Learning for Students with Dyslexia - Miftahul Jannah; Ernita Daulay (Journal of Educational Sciences, 2026)
Students with dyslexia often experience difficulties in reading, writing, and spelling, requiring instructional approaches that accommodate their diverse learning needs. Multisensory learning has been widely recognized as an effective approach because it integrates visual, auditory, kinesthetic, and tactile modalities to support literacy development and student engagement. This study aimed to analyze teachers’ efforts and challenges in implementing multisensory learning for students with dyslexia in an inclusive classroom. A descriptive qualitative case study was conducted at an inclusive Islamic junior high school in Medan, Indonesia, involving one English teacher and one inclusion support teacher. Classroom observations focused on four Grade VII students with dyslexia across three instructional sessions, each lasting approximately 45 minutes. Data were collected through classroom observations, lesson plan (RPP) documentation, and semi-structured interviews, and analyzed using the Miles and Huberman interactive analysis model. The findings revealed that teachers implemented multisensory learning through varied instructional media, individualized assistance, experiential learning activities, and collaboration with parents and peers. However, teachers encountered challenges related to limited instructional time, preparation of diverse learning media, differences in students’ learning abilities, and maintaining students’ attention and motivation. These findings highlight the importance of adaptive multisensory instruction in supporting inclusive education.